If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying h + -4h = 0 Combine like terms: h + -4h = -3h -3h = 0 Solving -3h = 0 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Divide each side by '-3'. h = 0 Simplifying h = 0
| 18a+7-11a= | | 3m-9-1=24 | | 4x^2=70 | | 6.4+4x=3.8x+7.6 | | -28=4(y-5)-8y | | 40+10e=2e-15 | | -7=-3(-7)+5 | | (-12h^4+h)-(-6h^4+3h^2-4h)= | | 2x=.2x+9 | | 5x-3x+8+3y-2y-7= | | 60-x=13x | | 55=-3-4k | | 3(7-13)=x-8 | | 10+10e=2e-15 | | 4x^2+15x+12=0 | | 4y+16=-3x | | 44x+2=2+44x | | 17x-8=14x+7 | | x^3-2x+56= | | 4x-2y=-2 | | 7=6x-5x+5 | | 19+-23= | | 18-6x=-22 | | 90x+30(90)=80x+80(90) | | 5(x+2)-3=4x+5 | | [24.6+3a]=9.54 | | 7x-3x+7+9y-8y-2= | | 0.90x+0.03(90)=0.08(x+90) | | 5b-b= | | 5=9y-8y+6 | | 8p^2+41p-184=0 | | 2-4u=-26 |